1398 Active Surveillance Vs. Partial Nephrectomy in Small Renal Masses: Overall and Cancer Specific Survival in A Retrospective Single Centre Study. (12th October 2021) - Shafi, S; Kouli, O; Nabi, G
Abstract: Introduction: Currently, the gold standard for T1a renal cell carcinoma treatment is partial nephrectomy (PN). However, active surveillance (AS) is increasing in elderly individuals with co-morbidities. Our hypothesis was that individuals choosing active surveillance would have similar cancer specific survival as partial nephrectomy. Method: This retrospective study used electronic notes to collect patient data presenting with T1a renal cell carcinoma, identified over a 15-year period. Primary outcomes were to compare the survival outcomes of these patients while being related to their comorbidities using the Charlson Comorbidity Index (CCI). Results: 183 patients were identified with 62 (35%) and 121 (65%) undergoing PN and AS respectively. Patients treated with AS were older (mean age of 66 years vs 58 years; P < 0.001 ) and had a higher CCI (median CCI 3 vs 2; P = 0.001 ). Overall, a total of 4 (6.5%) and 55 (45.5%) patients died from any cause after PN and AS respectively, with deaths attributed to kidney cancer was 2 (3.2%), and 10 (8.2%) respectively. Multivariate analysis showed only age >70 affected overall survival independently between the two groups (HR 5.85; CI 3.29-10.42; P < 0.001). Tumour size showed to be the only independent variable on cancer specific survival ( HR 2.51; CI 1.14 -5.53; P = 0.023 ). No difference was seen between the treatment options in multivariate analysis in both overall and cancer specific survival. Conclusions: The study agreed with the hypothesis of similar cancer specific survival. Highlighting for elderly individuals with significant co-morbidities, there is no observed benefit for undergoing partial resection.